Efficient removal of estrone and 17β-estradiol from aqueous medium using UV irradiation-assisted fenton process - Dikmen, Yaren; Saylan, Meltem; Oflu, Sude; Ayyildiz, Merve Firat; Serbest, Hakan; Bozyigit, Gamze Dalgic; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2024)
The endocrine-disrupting compounds (EDCs) have high-risk implications for public health and the environment due to their potential to interfere with endocrine system functions. This study is based on an evaluation of the applying the UV-assisted Fenton process for the removal and degradation of 17 beta-estradiol and estrone in aqueous medium. The simple and affordable UV irradiation system was developed and applied to accelerate the Fenton reaction. High performance liquid chromatography (HPLC) was employed for the quantitative measurements of estrogenic hormones at 230 nm, which is highly sensitive and capable of accurately measuring hormones within 15 min. The LOD/LOQ values of HPLC system were recorded to be 0.03/0.11 mg/kg and 0.05 /0.15 mg/kg for estrone and 17 beta-estradiol, respectively. Fe3O4 magnetic nanoparticles and iron (II) sulfate solution were evaluated as appropriate iron sources under fixed UV irradiation to assess the Fenton process. The main parameters, namely hydrogen peroxide (H2O2) amount, iron (II) sulfate amount, pH, and UV irradiation period, were optimized univariately for determining the optimum conditions. The optimum conditions were recorded to be: 0.70 mL of pH 3.0 buffer solution, 1.25 mL of H2O2, 0.80 mL of 100 mg/L Fe2+ solution, and an irradiation time of 60 min. The removal experiments were also carried out on domestic wastewater to validate the system's applicability. The percent removal efficiencies of both estrogenic hormones were calculated at higher than 99%. These results showed that high efficiency was achieved within the detection limits of the HPLC system. This proves the possibility of complete degradation of the analytes and their efficiency and practicality for pollution control and water quality improvement in future studies.
Keywords: 17 beta-estradiol; Estrone; UV degradation; Fenton reagent; Domestic wastewater; ENDOCRINE DISRUPTING COMPOUNDS; WATER; ESTROGENS; DEGRADATION; PHARMACEUTICALS; NANOPARTICLES; ESTRADIOL; OXIDATION; HORMONES; SERUM; Chemistry